Taḥlīl Akhṭā’ al-Aṣwāt al-ʿArabiyyah fī Mahārah al-Qirā’ah - Maratun Hamidah; Yelfi Dewi S (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
This letter was submitted on the topic “Analyzing the Errors of Arabic Sounds in Reading Skill.” The object of this research is the students other than the department of Arabic language education at the state Islamic University of Bukittinggi are not able to pronounce the letters of the convergent sound, and then the department of Arabic language education at the state Islamic university of Bukittinggi, who are not able to pronounce all the alphabets. Then the type of this research is qualitative and descriptive. The data of this research are the result of the recording of students who read Arabic texts, and the data sources for this research are the students of the college of education and educational science, other than the department of teaching Arabic, using the snowball sampling technique. The research results show that the wrong form in reading Arabic texts is the changes in the sound of the analysis of errors. Analysis of student mistakes in the letter ظ becomes the letter ز and ج, the letter ط, becomes the letter ت, the letter ض becomes the letter د, the letter ث becomes the letter س, ش, and the letter ذ becomes the letter ز, ج, the letter ح becomes the letter ه, the letter ز becomes the letter س, the letter ع becomes the letter ء, and the letter ش becomes the letter س.هذه الرسالة قدمت بموضوع "تحليل أخطاء الأصوات العربية في مهارة القراءة".  الهدف من هذا البحث هو الطلاب غير قسم تعليم اللغة العربية بجامعة بوكيت تنجي الإسلامية الحكومية غير القادرين لنطق الحروف العربية المتقاربة صوتها و غير المستطيعين في نطق الحروف الهجائية كلها. ثم نوع هذا البحث هو نوعي و وصفي، و بيانات هذا البحث هي نتائج تسجيلات أو تسجيلات صوتية للطلاب الذين يقرؤون النصوص العربية، ومصادر البيانات هذا البحث هو الطلاب لكلية التربية وعلوم التعليمية التخصوصية لغير قسم تعليم اللغة العربية باستخدام تقنيقية أخذا العينات من كرة الثلج. هذه النتائج تبين أن الشكل الخطأ في قراءة النصوص العربي هو التغيرات في صوت الحروف. أما الشكل لتحليل الأخطاء يكون في صوت الحروف العربية. تحليل أخطاء الطلاب يكون في حرف الظاء "ظ" يصبح حرف الزاي و الجيم "ز،ج"، وحرف الطاء "ط" يصبح حرف التاء "ت"، وحرف الضاد "ض" يصبح حرف الدال "د"،  وحرف الثاء "ث" يصبح حرف السين و الشين "س، ش"،  وحرف الذال "ذ" يصبح حرف الزاي و الجيم "ز،ج"، وحرف الخاء "خ" يصبح حرف الحاء "ح"، وحرف الحاء "ح" يصبح حرف الهاء "ه"، وحرف الزاي "ز" يصبح حرف السين "س"، وحرف العين "ع" يصبح حرف الألف "أ"، وحرف الشين "ش" يصبح حرف السين "س".